Is the Industrial Policy Suitable for the Industrial Chain? A Case Study from the Photovoltaic Industry in China—Evidence from Shenzhen - Yin Li; Yazhi Song; Qi Qin (Energies)
Shenzhen is a pilot pioneer in China. Developing the photovoltaic industry is an important area for Shenzhen to address climate change; thus, the Shenzhen’s government issued a series of support policies. However, does the released policy promote the development of the Shenzhen photovoltaic industry? Starting from the guiding mechanism of industrial policy on the development of the industrial chain, this paper discusses the compatibility between industrial policy and the development of the industrial chain. Through the analysis of Shenzhen photovoltaic industry data, it is found that the total factor productivity of the Shenzhen photovoltaic industry is twice that of the Yangtze River Delta and the Pearl River Delta, and the life cycle of the industrial chain is lower than the national average. However, the concentration of Shenzhen’s photovoltaic industry in 2021 was less than two-thirds of that in 2013, and it is still declining. At the same time, Shenzhen has obvious advantages in the photovoltaic industry market, but the compatibility of industrial policies is insufficient. Therefore, the overall policy suitability of Shenzhen’s photovoltaic industry is poor. The policy adjustment should be based on improving the concentration of the regional photovoltaic industry and realizing the leapfrog development of the industry by encouraging photovoltaic enterprises to extend to both ends of the industrial chain.